Genetic mapping of resistance to bacterial blight disease in cassava (Manihot esculenta Crantz) - Jorge, V.; Fregene, Martin A.; Duque E., Myriam Cristina; Bonierbale, Merideth W.; Tohme, Joseph M.; Verdier, Valerie M. (Springer, 2000)
Cassava bacterial blight (CBB), caused by Xanthomonas axonopodis pv. manihotis (Xam), is a major disease of cassava (Manihot esculenta Crantz) in Africa and South America. Planting resistant varieties is the preferred method of disease control. Recent genetic mapping of an F1 cross (TMS 30572 × CM 2177–2) led to the construction of the first molecular genetic map of cassava. To better understand the genetics of resistance to CBB, we evaluated individuals of the F1 cross for CBB resistance by controlled greenhouse inoculations and visually assessed symptoms on days 7, 15, and 30 days after inoculation, using a scale where 0 = no disease and 5 = maximum susceptibility. Five Xam strains were used: CIO-84, CIO-1, CIO-136, CIO-295, and ORST X-27. Area under the disease progress curve (AUDPC) was used as a quantitative measure of resistance in QTL analysis by single-marker regression. Based on the AUDPC values, eight QTLs (quantitative trait loci), located on linkage groups B, D, L, N, and X of the female-derived framework map, were found to explain 9–20% of the phenotypic variance of the crop’s response to the five Xam strains. With the male-derived framework map, four QTLs on linkage groups G and C explained 10.7–27.1% of the variance. A scheme to confirm the usefulness of these markers in evaluating segregating populations for resistance to CBB is proposed.